Endogenously modified multi-bioresponsive silk fibroin nanoparticles enhancing the cellular delivery and anti-inflammatory activity of curcumin - Sheliang Zhao; Yuwei Sun; Yuxuan Du; Mengjie Yang; Chenxu Gao; Yunshu Ge; Dongning Li; Yang Yang; Xuebo Liu (Food Research International, 2026)

Potential Causes of Anti‐Phase Summer Precipitation Variability Between the Middle and Lower Reaches of the Yangtze River - Yuwei Zhou; Ge Liu; Xiaolu Yan; Sulan Nan; Ting Zhang; Yinghan Sang; Xuefeng Han; Yuhan Feng; Hancheng Zou (International Journal of Climatology, 2026)
Summer precipitation in the middle and lower reaches of the Yangtze River generally shows synchronous variability and is thus extensively studied as a unified climatic region. However, out‐of‐phase variations occur between the middle and lower reaches in some years. This study investigates the mechanisms of the positive middle Yangtze River precipitation (MYRP)–negative lower Yangtze River precipitation (LYRP) pattern from the perspectives of atmospheric circulation and land‐ocean thermal anomalies. The results suggest that a non‐canonical Silk Road Pattern (SRP) teleconnection in the upper troposphere, coupled with a mid‐to‐lower tropospheric anomalous anticyclone over Northeast Asia and a weakened western Pacific subtropical high (WPSH), contributes to this precipitation pattern. Further analysis reveals that colder‐than‐normal land thermal anomalies in the Greater Caucasus Mountains and the northeastern Tibetan Plateau, as well as warmer‐than‐normal sea surface temperature anomalies (SSTAs) in the Sea of Japan, may help maintain the SRP‐like Rossby wave train (SLWT), therefore influencing the positive MYRP–negative LYRP pattern. Linear baroclinic model sensitivity experiments further support the identified thermal anomalies can excite and maintain the SLWT. Given that the SLWT differs to some extent from the classical SRP in both wave source and downstream structure, this study also proposes a SLWT index based on 200‐hPa vorticity anomalies. This index effectively captures both the spatial structure of the SLWT and its link with out‐of‐phase precipitation anomalies between the middle and lower reaches of the Yangtze River and may serve as a potential indicator for the occurrence probability of the positive MYRP–negative LYRP pattern. These findings may improve our understanding of regional precipitation mechanisms in the Yangtze River basin, thereby providing a scientific basis for improved disaster prevention and mitigation strategies.

Ultrasound-assisted extraction of peptidoglycan from Lactiplantibacillus plantarum: Structural characterization, anti-browning enhancement, and immunomodulatory effects - Yuwei Sun; Kemin Guo; Peiyun He; Dongning Li; Yunshu Ge; Guoqiang Zhang; Xuebo Liu (Food Chemistry, 2026)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

The Tibetan Plateau Westerly Jet Stream During July–August and Its Linkage With Precipitation in the Tibetan Plateau - Yuhan Feng; Sulan Nan; Ge Liu; Jingpeng Liu; Ting Zhang; Yuwei Zhou (International Journal of Climatology, 2025)
Using gridded and station‐observed precipitation datasets from the China National Meteorological Information Center, GPCC precipitation data, and ERA5 reanalysis data from 1980 to 2021, this paper identifies a westerly jet to the north of the Tibetan Plateau (TP) during July–August, which differs from the typical East Asian westerly jet and is named the TP jet (TPJ). The relationship between the meridional location of the TPJ and precipitation in the TP and the associated mechanism are investigated. The results show that the TP precipitation is closely related to the meridional location of the TPJ. When the TPJ is located farther north, more‐than‐normal precipitation occurs in the central‐western TP, and less‐than‐normal precipitation occurs in the southern part of eastern TP, thereby constituting an east–west antiphase mode. This mode is reversed when the TPJ is located farther south. The four‐quadrant conceptual model of the jet stream can explain the link between the location of the TPJ and the mode of TP precipitation. When the TPJ is farther north, an anomalous meridional‐vertical circulation cell appears at the entrance of the TPJ, with the central‐western TP located at the upward branch of this cell. The upward motion is conducive to the convergence of water vapour and the increase in total cloud cover and produces more‐than‐normal precipitation in the central‐western TP. Meanwhile, an anomalous meridional‐vertical circulation cell appears at the exit of the TPJ, which is opposite to that at the TPJ entrance. The downward branch of this anomalous cell governs the southern part of eastern TP, causing water vapour divergence and suppressing total cloud cover and precipitation. The results suggest that the TPJ should be considered a special system when exploring the cause of TP summer precipitation.

Modulation of Preceding Tibetan Plateau Tropospheric Thermal Anomaly on Summer Temperature Anomalies in the Yangtze and Huaihe River Valleys - Di Li; Ting Zhang; Ge Liu; Jingpeng Liu; Changyan Zhou; Dongmei Qi; Yuhan Feng; Yuwei Zhou (International Journal of Climatology, 2025)
Anomalous warm surface air temperatures (SATs) appeared in eastern China, especially the middle and lower Yangtze and Huaihe River valleys (MLYHRV), in the summer of 2022. Using the 2022 SAT anomaly as a case, this study analyses the reasons for the variation of summer SATs in the MLYHRV and explores the precursory signals for the summer MLYHRV SAT and related mechanisms. The findings indicate that the preceding May mid‐upper (500–300 hPa) tropospheric temperature (TT) over the Arabian Sea and India and the western Tibetan Plateau (TP) can reflect the persistence of the TT anomaly over the western TP and its eastward extension to the Japan Sea from May to summer, which causes downstream East Asian circulation (i.e., the South Asian high and western Pacific subtropical high) and related SAT anomalies over the MLYHRV during summer (especially July–August). In addition, the May La Niña SST can reflect the summer La Niña SST pattern and therefore affect the summer MLYHRV SAT by modulating the East Asian circulations. Using TT and SST precursory signals, a statistical prediction model was developed to predict the summer MLYHRV SAT. This model based on the TT and SST signals shows better prediction ability than the model based only on the traditional La Niña SST signal. The May ASI‐WTP TT may be regarded as a crucial supplementary precursor for forecasting the summer MLYHRV SAT.

Synergistic contribution of soil moisture and sea surface temperature to summer Tibetan Plateau temperature - Ting Zhang; Ge Liu; Mingkeng Duan; Yuhan Feng; Yuwei Zhou; Xin Mao; Xinchen Wei; Jingxin Li (Atmospheric Research, 2025)

Trend and potential enhancement of cropping intensity - Tingting He; Maoxin Zhang; Wu Xiao; Ge Zhai; Kai Fang; Yuwei Chen; Cifang Wu (Computers and Electronics in Agriculture, 2025)

Environmental DNA integrity index is sensitive for species biomass estimation in freshwater - Qinyu Ge; Yanyan Piao; Zhihui Li; Yuwei Yang; Min Pan; Yunfei Bai (Science of The Total Environment, 2025)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Precursory signals of summer precipitation over southern Central Asia: Combined effect of April soil moisture and sea surface temperature - Xinchen Wei; Ge Liu; Sulan Nan; Ting Zhang; Xin Mao; Yuhan Feng; Yuwei Zhou (International Journal of Climatology, 2024)
This study investigates the interannual variability of summer precipitation over Central Asia and explores its precursory signals through soil moisture (SM) and sea surface temperature (SST) anomalies. The results reveal that southern Central Asia (SCA) is a crucial SM‐precipitation coupling region where summer precipitation is significantly linked to the preceding April SM in the Turan Plain, between the Caspian Sea and the Tibetan Plateau. The preceding Turan Plain SM (TPSM) anomaly can reflect the ensuing summer SM anomalies in the SCA region due to the persistence of SM. The higher TPSM can stimulate anomalous convective ascent and associated negative geopotential height anomalies over the SCA region, which is favourable for more SCA precipitation (SCAP) during summer. Additionally, Indian and Pacific Ocean SST (IPOS) anomalies can regulate the summer SCAP through ocean and land relay effects. The preceding April can reflect the subsequent summer SST anomalies across the northern Indian Ocean and South China Sea, which trigger a Matsuno‐Gill response and induce anomalous water vapour transport into the SCA region, providing favourable moisture conditions for more SCAP during summer. Apart from such an ocean relay effect, the preceding IPOS can modulate the April TPSM first and then affect the summer SCAP through the land relay effect caused by persistent SM anomalies from April to summer. The combined effect of the preceding TPSM and IPOS on the summer SCAP is more pronounced than the respective effect of either TPSM or IPOS. Incorporating the TPSM signal as a supplementary precursor can enhance the predictive skill of summer SCAP. These findings may provide valuable insights into the reasons and prediction of the variability of summer SCAP.

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Contribution of sea surface temperature anomalies in the Barents and Yellow-Japan Seas to summer high temperature anomalies over the eastern Tibetan Plateau - Ting Zhang; Ge Liu; Mingkeng Duan; Xin Mao; Xinchen Wei; Yuhan Feng; Yuwei Zhou; Jingxin Li (Atmospheric Research, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Effect on Serum Parameters and Immune Responses of Carassius auratus gibelio Exposed to Dietary Lead and Bacillus subtilis - Yanan Cai; Yuwei Yin; Longtao Wang; Dongze Leng; Chenxia Ge; Abedin Abdallah; Yuehong Li (Biological Trace Element Research, 2019)

Immunopotentiator Thymosin Alpha-1 Promotes Neurogenesis and Cognition in the Developing Mouse via a Systemic Th1 Bias - Ge Wang; Fen He; Yunlong Xu; Yuwei Zhang; Xiao Wang; Chunhua Zhou; Yihong Huang; Juntao Zou (Neuroscience Bulletin, 2017)